17 Presentation of Capras syndrome in anti-NMDA receptor encephalitis: a neuro-rehabilitation approach. Issue 8 (20th July 2020) - Francis, Richard; Ching, Hui; Tyagi, Himanshu; Swayne, Orlando; Ajina, Sara; Monaghan, Bernadette
Abstract : Objectives/Aims: Capgras syndrome is not often seen in neuro-rehabilitation and few case-reports of Capgras syndrome after anti-NMDA receptor encephalitis exist in literature. This case is relevant in light of how the Capgras sydrome and delusional beliefs affected this patient's discharge planning, engagement with the multi- disciplinary team during rehabilitation and side-effects of pharmacological management. The challenging aspects of the case revolve around the patient's persecutory beliefs, his delusional misidentifation disorder and its subsequent management. Methods: The patient is a middle-aged gentleman with a background of relapsing- remitting multiple sclerosis who presented with seizures, headache, rash and intermittent fevers. He was initially treated as infectious meningoencephalitis and his condition deteriorated due to combination of behavioural change and seizures. A MRI-head suggested viral encephalitis but lumbar puncture and serum showed strongly positive for anti-NMDA receptor antibodies, thought potentially secondary to the patient's disease-modifying drugs for his multiple sclerosis. After step-down from Intensive Care, the patient was noted to have fixed persecutory delusions regarding his wife and children. He believed that his wife and children were imposters and that the hospital and doctors within it were conspiring against him. He was managed initially with risperidone however the dose could not be increased due to the sedating side-effects resulting in an inability to engage with rehabilitation. He was subsequently changed to aripiprazole and escitalopram with the intention to decrease his delusional misidentification disorder. His delusions partially resolved with the patient accepting his children as his own, but not accepting his wife as truly 'his wife'. The discharge destination represented a difficulty due to concerns that he may become aggressive (physically/verbally) to his wife if he continued to deem her an 'imposter'. The patient was managed by sidestepping the conflict; he was more accepting of his wife if introduced as a 'friend who loves him'. The patient was also allowed to drive the narrative rather than forced to deal with his Capgras syndrome. Results: A discharge home with support (including his wife) became feasible as his delusion thawed. Conclusions: Managing complicated patients like this involves not only pharmacological options but also psychological/psychiatric intervention and employment of non-confrontational techniques to help better engagement with rehabilitation.